HUBUNGAN STATUS GIZI DAN TEKANAN DARAH PADA LANSIA: ANALISIS INDEKS MASSA TUBUH DAN RISIKO HIPERTENSI DI UPTD PUSKESMAS MOKOAU - Sahumena, Muhamad Handoyo; Ihsan, Sunandar; Trinovitasari, Nita; Irmasari, Irmasari; Pebriyanti, Citra; Putri, Fadilah Septiana; Rahmawati, Islah; Hamid, Asmida; Saputri, Cahyati; Fadhillah, Nurul Aliah; Uciliana, Wa (BESIRU : Jurnal Pengabdian Masyarakat, 2025)
Hypertension is one of the most prevalent non-communicable diseases among older adults and has the potential to cause serious complications such as stroke and heart disease. This community service activity aimed to improve the knowledge, awareness, and healthy behaviors of older adults through health education and routine health screenings at the Elderly Posyandu of UPTD Puskesmas Mokoau. The methods included Body Mass Index (BMI) assessment, blood pressure measurement, health counseling, and educational sessions on hypertension prevention and control. A total of 20 older adults participated in the program. The results showed that 40% of participants were overweight or obese, and 50% were classified as having stage 2 hypertension. These findings indicate a strong relationship between nutritional status and hypertension risk. Health education was found to increase awareness regarding healthy lifestyle practices, the importance of regular blood pressure monitoring, and the management of risk factors. This activity demonstrates that collaboration between the Community Health Center, the Elderly Posyandu, and healthcare workers plays a significant role in promotive and preventive efforts to address hypertension among older adults.